STABILIZATION OF THE BOUNDARY TO A HYPERBOLIC SYSTEM - Pérez Salvatierra, Alfonso (2004)
In therse notes we will study the decay velocity of the energy of the hyperbolic systems solutions with dissipative contour conditions.